Revisão das espécies neotropicais de Chaetoravinia Townsend, 1917 (Diptera, Sarcophagidae) - Guimarães, Hugo José Lopes (1998)
This dissertation presents the taxonomic revision of the neotropical species of Chaetoravinia Townsend, 1917 (Diptera, Sarcophagidae ). According to DODGE (1968) and LOPES (1969, 1976, 1977, 1978) ten species are recognized to the neotropical region: Chaetoravinia advena (Walker, 1852), Chaetoravinia almeidai Lopes, 1946, Chaetoravinia barroi Dodge, 1956, Chaetoravinia dampfi Lopes, 1946, Chaetoravinia derelicta (Walker, 1852), Chaetoravinia effrenata (Walker, 1861), Chaetoravinia errabunda (Wulp, 1895), Chaetoravinia globulus (Aldrich, 1916), Chaetoravinia postnoda Dodge, 1968 and Chaetoravinia vagabunda (Wulp, 1895). Male redescriptions are presented and are accompanied by the terminalia illustrations, including important characteres used in the definition of the species, not mentioned by the former authors in their descriptions or revisions, as: hillae, dorsal rods and median process. A key for male identification of the neotropical species of Chaetoravinia is also presented. According to the detailed study of the male terrninalia, two informal groups of species were recognized based on the morfological similarities: "advena group" and "derelicta group".